2006
DOI: 10.2343/geochemj.40.87
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and kinetics of reactions between C1-C3 hydrocarbons and calcium sulfate in deep carbonate reservoirs

Abstract: Organic-inorganic reactions during thermochemical sulfate reduction (TSR) are the main cause for the destruction of hydrocarbons in deep carbonate sediments. In this paper, thermal simulation experiments on C 1 -C 3 hydrocarbons and solid calcium sulfate were carried out using an autoclave operated at high temperature and high pressure. The gas and solid products were characterized by advanced analytical methods including microcoulometry, gas chromatography and FT-IR. The kinetics and thermodynamics were inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 25 publications
(27 reference statements)
2
21
1
Order By: Relevance
“…Tang et al [38] reported that MgSO 4 is an effective oxidant of hydrocarbons without the addition of initial ARTICLES GEOCHEMISTRY hydrogen sulfide which has been used as an initiator in other experiments [22,23] . The apparent activation energy of the reaction between methane and magnesium sulphate is 101.894 kJ/mol, which is lower than most previous studies (121-208 kJ/mol) [17,18,20,24,25] . This value is close to that calculated by Goldhaber and Orr [23] in the presence of high H 2 S (96 kJ/mol), which to some extent justifies Tang's viewpoint.…”
Section: Discussioncontrasting
confidence: 52%
See 4 more Smart Citations
“…Tang et al [38] reported that MgSO 4 is an effective oxidant of hydrocarbons without the addition of initial ARTICLES GEOCHEMISTRY hydrogen sulfide which has been used as an initiator in other experiments [22,23] . The apparent activation energy of the reaction between methane and magnesium sulphate is 101.894 kJ/mol, which is lower than most previous studies (121-208 kJ/mol) [17,18,20,24,25] . This value is close to that calculated by Goldhaber and Orr [23] in the presence of high H 2 S (96 kJ/mol), which to some extent justifies Tang's viewpoint.…”
Section: Discussioncontrasting
confidence: 52%
“…Properties of the solid phase were analyzed by FT-IR and X-ray diffraction. MgO had not been found in the blank tests, which showed that there was no hydrolysis of According to the former simulation experiments on C 1 -C 3 hydrocarbons and solid calcium sulfate [25] , long-chain hydrocarbons more easily participate in the reactions than short-chain hydrocarbons. Ethane should be more active than methane in the process of TSR.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations